Caracteristicas de discos debris en Enanas Blancas - Saker, L; Gómez, Mercedes; Chavero, Carolina Andrea (Asociación Argentina de Astronomıa, 2021)
Abstract: In the late ’80s an infrared excess (IR) around a white dwarf star (WD) was detected, which was attributed to the presence of a dusty circumstellar disk. In recent years, thanks to Spitzer, the number of WDs with excesses has increased significantly. In this contribution we present the modeling of the spectral energy distributions (SEDs) of a sample of 29 WDs having IR excesses. This model allows us to derive the mass and the internal and external radii of the dusty disk, for a given chemical composition. The location of this ring is compared with the Habitability Zone (HZ) of each WD in the sample. In addition, the dimensions and masses of these rings are compared with those around main sequence stars, commonly known in the literature as debris disks.